2008
DOI: 10.1080/15257770802143897
|View full text |Cite
|
Sign up to set email alerts
|

ITPase Activity in Dry Blood Spots is Comparable with That in Fresh Erythrocytes

Abstract: Inosine triphosphate pyrophosphohydrolase (ITPase) catalyzing the pyrophosphohydrolysis of inosine triphosphate, deoxyinosine triphosphate and xanthosine triphosphate is involved in the metabolism and tolerance of thiopurine drugs. ITPase activity plays an important role in the prediction of toxicity to thiopurine therapy. Activities in dry blood spots were compared with fresh erythrocytes. Samples were incubated with inosine triphosphate, then inosine monophosphate was determined by a capillary electrophoresi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…Most studies on ITPase activity and function used erythrocyte lysates (11)(12)(13). However, Sumi et al showed in a control population that ITPase activity in leukocytes is higher when compared to erythrocytes (14).…”
mentioning
confidence: 99%
“…Most studies on ITPase activity and function used erythrocyte lysates (11)(12)(13). However, Sumi et al showed in a control population that ITPase activity in leukocytes is higher when compared to erythrocytes (14).…”
mentioning
confidence: 99%